Comparison of alkaline stability of benzyltrimethylammonium, benzylmethylimidazolium and benzyldimethylimidazolium functionalized poly(arylene ether ketone) anion exchange membranes. (30th January 2016) - Wang, Baolong; Sun, Wenmo; Bu, Fanzhe; Li, Xuefeng; Na, Hui; Zhao, Chengji
Abstract: The alkaline stability of benzyltrimethylammonium, benzylmethylimidazolium and benzyldimethylimidazolium functionalized poly(arylene ether ketone) anion exchange membranes (AEMs) were investigated by conductivity change and NMR experiments. The corresponding small molecular model compounds were synthesized and used to determine the degradation degree of benzyltrimethylammonium, benzylmethylimidazolium and benzyldimethylimidazolium cations. The results showed only 7% of benzyltrimethylammonium model compound degraded in 1 M NaOH at 60 °C; whereas, benzylmethylimidazolium and benzyldimethylimidazolium model compounds had a degradation of 55% and 46% at the same condition, respectively. The alkaline stability of three cations follows the order: benzyltrimethylammonium > benzyldimethylimidazolium > benzylmethylimidazolium. The NMR spectra and hydroxide conductivity change with immersing time in 1 M NaOH at 60 °C also confirmed that benzyltrimethylammonium functionalized polymer had a relative better alkaline stability than benzylmethylimidazolium and benzyldimethylimidazolium functionalized polymers in alkaline environment at elevated temperature. This research enriches the investigation on the alkaline stability of anion exchange membranes with quaternary ammonium, imidazolium and C2-substituted imidazolium. Graphical abstract: Highlights: Quaternized polymer membranes and three model compounds were prepared. The alkaline stability was detailed compared. Benzyltrimethylammonium based membranes had the better alkaline stability.